Friedrich Nietzsche and Fyodor Dostoyevsky on Solitude. - Stoute, Martin (My University, 2000)
This paper is an examination of the themes of solitude and community in Friedrich Nietzsche's Thus Spoke Zarathustra and Fyodor Dostoyevsky's The Brothers Karamazov. I will argue that there are both areas of convergence and divergence in their treatment of social relations in terms of solitude, isolation and community. Generally speaking, Dostoyevsky diverges from Nietzsche in advocating a humble "active love" towards society, which is capable of moral and spiritual regeneration. Nietzsche has a much more selective conception of higher society, deeming the bulk of society hopelessly fallen. Whereas Dostoyevsky is drawn towards the people, Nietzsche is drawn towards the able few. Despite the areas of divergence, however, I believe that the areas of convergence are more profound. Both men argue that isolation in its various forms is one of society'S greatest problems. This isolation can be overcome only through the cultivation of solitude and genuine community.
Keywords: Philosophy; Philosophy